2022
DOI: 10.35848/1882-0786/ac5724
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dislocation density in lattice-relaxed Al0.68Ga0.32N film grown on periodical 1 μm spacing AlN pillar concave-convex patterns and its effect on the performance of UV-B laser diodes

Abstract: We report the results of crystal growth of thick AlGaN films on periodical 1 μm-spacing AlN pillar concave-convex patterns and its impact on the performance of UV-B laser diodes. The formation of voids in the AlGaN film by increasing the AlN pillar height and the use of high quality AlN templates were effective in improving the quality of AlGaN, and the dislocation density in the AlGaN film was reduced down to approximately 3.4 × 108 cm−2. A gain-guided UV-B laser diode was fabricated on the optimized AlGaN, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…This gap has a distinct correlation with threading dislocation densities typical for AlGaN alloys, which were shown in Figure 1 of the review reported in [ 24 ]. This correlation reveals a very critical effect of threading dislocation density (TDD) on the threshold current density of DUV-LDs, which was further confirmed by direct measurements reported in [ 25 , 28 , 29 , 30 ], see Figure 2 a (TDD for the lowest threshold current density shown in this figure was not reported in [ 25 ], but we estimated TDD in the range of ~10 6 –10 7 cm −2 ). The efforts aimed at TDD reduction, thus improving the threshold current density, will be discussed in more detail in Section 2 .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This gap has a distinct correlation with threading dislocation densities typical for AlGaN alloys, which were shown in Figure 1 of the review reported in [ 24 ]. This correlation reveals a very critical effect of threading dislocation density (TDD) on the threshold current density of DUV-LDs, which was further confirmed by direct measurements reported in [ 25 , 28 , 29 , 30 ], see Figure 2 a (TDD for the lowest threshold current density shown in this figure was not reported in [ 25 ], but we estimated TDD in the range of ~10 6 –10 7 cm −2 ). The efforts aimed at TDD reduction, thus improving the threshold current density, will be discussed in more detail in Section 2 .…”
Section: Introductionsupporting
confidence: 89%
“… ( a ) Experimental threshold current densities of UV laser diodes (symbols) fabricated by various approaches, including growth on concave-convex patterned AlN (PCCP AlN) vs. TDD [ 25 , 28 , 29 , 30 ]; the straight line approximates the data. ( b ) Measured internal quantum efficiency (symbols) of UV-LEDs emitting at various wavelengths as a function of TDD in the LED structure [ 31 , 32 , 33 ]; the solid line is the theoretical curve calculated by the model described in [ 34 ].…”
Section: Figurementioning
confidence: 99%
“…In this method, the HR and AR mirrors were formed on the edge surfaces of UV‐B laser diodes, and their performance was verified. In this study, we fabricated UV‐B laser diode wafers similar to the structure and fabrication method reported by Omori et al [ 17 ] For the mirrors used in this experiment, a combined method of Cl 2 ‐ICP and wet etching with the TMAH solution was used. [ 21 ] Additionally, experiments were conducted by controlling the AlN molar fraction of the quantum well active layer, enabling the oscillation wavelength to be ≈310 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Here, a UV-B laser diode was fabricated through two breakthroughs: the use of relatively high-quality AlGaN with lattice relaxation [11,12] and the application of polarization doping [13,14] to the p-AlGaN cladding layer to achieve favorable optical cavity formation and high-current-density injection. To improve the performance of the fabricated UV-B laser diode, we have optimized the growth conditions of spontaneously nucleated AlN, [15] applied AlN nanopillars, [16,17] increased the optical confinement factor Γ, [18] and applied a refractive index waveguide structure. [19] Meanwhile, UV-B laser diodes use a combination of Cl 2 -inductively coupled plasma (ICP) dry etching and wet etching with the TMAH solution to form flat m-plane facets, [20] which are then used as mirrors.…”
mentioning
confidence: 99%
“…[ 17 ] Two methods of fabricating the AlGaN templates suitable at RT have been reported, namely, the spontaneous nucleation [ 20,22,23 ] and AlN nanopillar, [ 21,24 ] and the achievable dislocation density is slightly lower in the AlN nanopillar method. [ 21 ] Meanwhile, it is difficult to find a clear difference for the J th of LDs, specifically when only the top data are compared. [ 21,23,25 ] Crystal defects other than dislocations may also affect the device performance.…”
Section: Introductionmentioning
confidence: 99%